Bioadsorción de Pb y Cr mediante la utilización de cáscara de naranja (Citrus Sinensis) molida, Machala 2014. - Ordóñez Romero, Annabell E. (2015)
In the present research aimed to determine the ability of bio sorption of heavy metals such as lead Pb and chromium Cr in flour orange peel that is then discarded the use of juice in juice stands central market canton Machala.